Distributed gateway-based load balancing in software defined network - Halimah Tussyadiah; Ridha Muldina Negara; Danu Dwi Sanjoyo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
To achieve an internet with high availability and reliability, needs two or more data paths so the process for sending data can be faster. Load balancing is often plays a significant role for this technique to properly utilized every gateway in the network. This research, implemented load balancing in software defined network architecture using floodlight controller. Evaluation is done by measuring QoS (delay, bit rate, packet rate, packet success rate) while sending various traffics through the network such as UDP Flow, VoIP, and DNS. Performance of load balancer is work well, because the results after load balancing is better than before. Which is the value of delay after load balancing is decreased about 30-55% compared to before load balancing, also the values of bit rate, packet rate dan packet success rate after load balancing is increased about 10-30% compared to before load balancing.